Proceedings of the 51st Hawaii International Conference on System Sciences 2018
DOI: 10.24251/hicss.2018.226
|View full text |Cite
|
Sign up to set email alerts
|

Emotions Trump Facts: The Role of Emotions in on Social Media: A Literature Review

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 92 publications
1
11
0
Order By: Relevance
“…Hyvä rinen and Beck (2018) have suggested this limitation. Based on a comprehensive literature review of the role of emotions in social media, they identified scarce research on the study of emotional factors to predict user engagement behaviors out of 82 reviewed papers [15]. Second, prior studies mainly used statistical data directly from the web pages or survey data from respondents to study extrinsic motivations without understanding the sentiment and opinions embedded in users' messages.…”
Section: User Knowledge Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hyvä rinen and Beck (2018) have suggested this limitation. Based on a comprehensive literature review of the role of emotions in social media, they identified scarce research on the study of emotional factors to predict user engagement behaviors out of 82 reviewed papers [15]. Second, prior studies mainly used statistical data directly from the web pages or survey data from respondents to study extrinsic motivations without understanding the sentiment and opinions embedded in users' messages.…”
Section: User Knowledge Contributionmentioning
confidence: 99%
“…Emotion can either refer to user's emotions toward individual activities or opinions toward products. Hyvä rinen and Beck (2018) suggest opinions should be differentiated from other emotions [15]. Both types of emotion response may exert influence on customer knowledge contribution behaviors.…”
Section: Emotional Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Happiness in an individual is not caused by a single element rather by multiple interplays of emotions that cause pleasures giving life satisfaction and social connectedness (Kringelbach & Berridge, 2010). Hyvärinen and Beck (2018) opined that emotions are entwined in people’s lives, an integral element for successful interaction (Wakefield & Wakefield, 2016). The four basic emotions that constitute the basic building block for perfect emotional well-being constitute happiness, sadness, fear/surprise and anger/disgust (Beck, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ten years after the article by Berry Richards which highlighted the emotional deficit in political communication (Richards, 2010), affects seem to be the holy grail for scholars who are dealing with media, election campaigns, and public discourse studies. Scholarly interest in emotions and political talks has increased over the past decade, with particular attention to the strategic and institutional ways in which emotions in politics are used and disseminated (Crigler and Just, 2012;Hissu and Beck, 2018;Jutel, 2017;Moss et al, 2020;Wahl-Jorgensen, 2019). There is a wide academic consensus on the emotive component of politics, and few would question that feelings and sentiments have effects on political communication and participation.…”
Section: Objectives Of the Thematic Issuementioning
confidence: 99%